The Utilization of Digital Flashcard in English Vocabulary Learning at Elementary School - Ronal Saputra; Maulina Maulina; Rahmat Nasrullah (Publikasi Indonesia, 2025)
In Indonesia’s elementary education, English vocabulary acquisition remains challenging due to limited exposure and traditional methods. Digital flashcards, recognized for their interactivity and accessibility, offer a potential solution, yet their efficacy in low-resource settings is underexplored. This study investigates the effectiveness of Canva-based digital flashcards in enhancing vocabulary comprehension among Grade I students at SD Negeri 50 Kendari, a school with minimal English proficiency. A pre-experimental one-group pretest-posttest design was employed with 24 students. Pretest and posttest data (10 multiple-choice questions) were analyzed using SPSS 16.0, including paired samples t-tests (α = 0.05). Results showed a significant increase in mean scores from 21.25 (pretest) to 46.25 (posttest) (p = 0.000), confirming digital flashcards’ effectiveness. However, external factors (e.g., motivation) were noted as limitations. The study underscores digital flashcards’ utility in resource-constrained contexts and advocates for further research on long-term retention, multimodal integration, and adaptive technologies. Practical contributions include a replicable model for teachers using Canva to create low-cost, engaging materials.